Effects of Losartan, Atorvastatin, and Aspirin on Blood Pressure and Gut Microbiota in Spontaneously Hypertensive Rats - Shuai Dong; Qi Liu; Xue Zhou; Yubo Zhao; Kang Yang; Linsen Li; Dan Zhu (Molecules, 2023)
Many studies have shown that alterations in the gut microbiota are associated with hypertension. Our study aimed to observe the characteristics of the gut microbiota in hypertension and to further explore whether drug molecules can play a therapeutic role in hypertension by interfering with the gut microbiota. We evaluated the differences in the composition of the gut microbiota in spontaneously hypertensive rats (SHR) and Wistar Kyoto rats (WKY). Meanwhile, three first-line cardiovascular disease (CVD) drugs, losartan, atorvastatin, and aspirin, were used to treat the SHR in order to observe their effects on the gut microbiota in SHR. The 16S rDNA results showed that the diversity and richness of the gut microbiota in SHR were significantly reduced compared with that of the WKY, the Firmicutes/Bacteroidetes ratio was increased, the abundances of Bifidobacterium and short chain fatty acids (SCFAs)-producing bacteria decreased, and the abundance of lactate-producing bacteria increased. In addition to lowering the blood pressure, losartan increased the abundances of Alistipes, Bacteroides, and Butyricimonas in SHR, reduced the abundances of Ruminococcaceae, Streptococcus, and Turicibacter, reduced the Firmicutes/Bacteroidetes ratio, and rebalanced the gut microbiota. Losartan also increased the abundances of Bifidobacterium and SCFAs-producing bacteria and reduced the abundance of lactate-producing bacteria. However, atorvastatin and aspirin had no significant effect on the gut microbiota in SHR. The above results showed that losartan could change the characteristics of the gut microbiota in hypertension and rebalance the gut microbiota, which may be related to lowering the blood pressure. Atorvastatin and aspirin have no significant influence on the gut microbiota in SHR.